2002
DOI: 10.1002/jbm.10146
|View full text |Cite
|
Sign up to set email alerts
|

Application of magnetic resonance microscopy to tissue engineering: A polylactide model

Abstract: Absorbable polymers are unique materials that find application as temporary scaffolds in tissue engineering. They are often extremely sensitive to histological processing and, for this reason, studying fragile, tissue-engineered constructs before implantation can be quite difficult. This research investigates the use of noninvasive imaging using magnetic resonance microscopy (MRM) as a tool to enhance the assessment of these cellular constructs. A series of cellular, polylactide constructs was developed and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 29 publications
(35 reference statements)
2
25
0
1
Order By: Relevance
“…Burg et al [54] previously reported a method to observe cellular distribution in a polymeric material (TR ¼ 600 ms, TE ¼ 11 ms, resolution 23 mm). Similar to our method, they observed that the signal intensity was higher in cells than in the liquid phase and scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…Burg et al [54] previously reported a method to observe cellular distribution in a polymeric material (TR ¼ 600 ms, TE ¼ 11 ms, resolution 23 mm). Similar to our method, they observed that the signal intensity was higher in cells than in the liquid phase and scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…While NMR imaging allows the assessment of structural features of the construct, localized NMR spectroscopy enables the evaluation of the number of viable cells and of the cellular metabolic state in a volume of interest (VOI) contained within the construct (Constantinidis and Sambanis, 1998;Constantinidis et al, 2001Constantinidis et al, , 2002Burg et al, 2002;Stabler et al, 2005a, b). For instance, the resonance of total cellular choline, measured by water-suppressed 1 H NMR spectroscopy, correlates positively and linearly with the viable cell number, hence it is a reliable estimate of the latter (Long et al, 2000;Stabler et al, 2005a, b).…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22] Information about cell distribution in tissue-engineered constructs and the characterization of cell-scaffold interactions provided by MR imaging indicates that MR imaging can be useful for examining polymer microstructure design and cell seeding. 23 The proton relaxation time of MR imaging is highly correlated to the glycosaminoglycan and collagen concentrations of cartilage matrix and engineered hyaline cartilage formation. 17,24,25 The change of the proton relaxation times also corresponds well with cartilage calcification and with mineralization level at the late stage of in vitro bone formation.…”
Section: Introductionmentioning
confidence: 99%